Religion and Women's Socioeconomic Welfare: An Empirical Study of Women's Economic Empowerment Based on Entrepreneurial Pesantren - Dharma Setyawan; Dwi Nugroho (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2022)
The purpose of this study is to reveal the role of women in building economic independence amid gender issues. The absence of religion and government in a connected business has made the issue of violence against women continue to roll on. The existence of women in recent years, and likely to continue, is threatened by the absence of safe spaces for women. Komnas Perempuan's 2020 data explains that in the last 12 years cases of violence against women and children have continued to increase significantly due to disharmony and economic factors. Using a phenomenological approach, this study shows a positive pattern in reducing the number of violence against women and realizing women's socio-economic welfare through the women's economic empowerment movement.